Evolution of Post‐Sunset EPBs: Relationships to the EIA Induced by Pre‐Reversal Enhancement Electric Fields - Lung‐Chih Tsai; Shin‐Yi Su; Harald Schuh; Mohamad Mahdi Alizadeh; Jens Wickert (Space Weather)
Abstract This paper presents Global Navigation Satellite System radio occultation (RO) observational analyses on deducing the relationships and dependences between post‐sunset equatorial plasma bubbles (EPB) occurrences and equatorial ionospheric anomaly (EIA) strength variability. The RO data were acquired from the FormoSat‐7/Constellation Observing System for Meteorology, Ionosphere and Climate 2 (FS7/COSMIC2) Program from 2020 to 2024. In this study, we incorporate both effects from crest peak electron density (Nemax) and crest‐to‐trough Nemax ratio and propose a new EIA strength parameter defined as the mean of northern and southern crest‐to‐trough Nemax differences to recognize and characterize the post‐sunset EIA features. Both seasonal–longitudinal appearances of intense post‐sunset EPB occurrences and strong EIA events occurred on more or less 30 days expanded from when and where magnetic flux tubes align with the sunset terminator at the magnetic equator but have more intense EPB and/or strong EIA days during southern (northern) hemispheric summers in the South American area (the Central Pacific area and the Africa area). It is well consistent with Tsunoda's hypothesis (Tsunoda, 1985, https://doi.org/10.1029/ja090ia01p00447) during the evening pre‐reversal enhancement and reveals more information on virtual day‐to‐day variability, intensities and extents of post‐sunset EPB occurrences and EIAs subject to seasonal, longitudinal, and solar cycle variabilities. Moreover, the local‐time evolutions of peak post‐sunset EIAs occurred during 19∼20 local time (LT) which is earlier than that of the obtained experimental peak (i.e., 20:20 LT) of post‐sunset EPB occurrences. We expect that the post‐sunset EIA detection could be one of the potential precursors for post‐sunset EPB occurrence.